Expert System for Detecting Early Symptoms of Gastroesophageal Reflux Disease (GERD) method Case Based Reasoning (CBR) Using Mobile Android - Rima Tamara Aldisa (Jurnal Mantik, 2021)
GERD is a chronic disease that occurs when stomach acid or bile flows into the food tract and irritates its inner walls. Acid reflux and heartburn. Symptoms include heartburn that usually occurs after eating and worsens when lying down. In designing this expert system is an application used to detect GERD disease. The process of helping detect begins with the way the user answers the questions in the form of symptoms suffered by the user. This expert system is based on Android so that it can be accessed anytime and anywhere by the user and this system is built using the Java Android programming language. The conclusions that can be obtained from the results of this study include the blackbox test results showing the features of the application that are made running. An expert system application designed to be able to help detect GERD based on the symptoms entered by the user.